Pelatihan Fungsionaris KSU 926 Saentis Meningkatkan Ketrampilan Menyusun Laporan RAT Berbasis Metakognisi Dan ICT - Rusmini Rusmini; Fitrah Sari Wahyuni Harahap (Pengabdian Deli Sumatera, 2022)
Multipurpose Cooperative (KSU) Deli Serdang Front Group 926 Saentis Village is a cooperative engaged in various business fields in Saentis Village which has difficulty in compiling a computer-based year-end report (RAT). Therefore, training and assistance are needed that aim to improve the skills of functionaries in preparing reports. The methods of training and mentoring at KSU are carried out in stages, meaning that each stage has different materials presented. This training and assistance is stage 2, namely stage 1 training for mothers who are members of cooperatives, namely sewing activities during the pandemic. Furthermore, because some of the functionaries did not understand computer-based data reporting, stage 2 was given training on how to understand something we already know and need to improve and something we have not mastered, namely in making year-end reports. The report was compiled based on ICT which aims to make the report valid and accepted at the annual member meeting. After training and mentoring, significant results were obtained where reports made based on metacognition and ICT were very valid and accepted at RAT.